2023
DOI: 10.3847/1538-3881/acc067
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Constraints on Planetary Companions to Nearby Sun-like Stars: An Archival Radial Velocity Survey of Southern Targets for Proposed NASA Direct Imaging Missions*  

Abstract: Directly imaging temperate rocky planets orbiting nearby, Sun-like stars with a 6 m class IR/O/UV space telescope, recently dubbed the Habitable Worlds Observatory, is a high-priority goal of the Astro2020 Decadal Survey. To prepare for future direct imaging (DI) surveys, the list of potential targets should be thoroughly vetted to maximize efficiency and scientific yield. We present an analysis of archival radial velocity data for southern stars from the NASA/NSF Extreme Precision Radial Velocity (EPRV) Worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 234 publications
(342 reference statements)
2
6
0
Order By: Relevance
“…Additionally, future work should include determining the depth of past searches for planets in these systems using archival photometry and public RV observations (e.g., Howard & Fulton 2016;Laliotis et al 2023). A follow-up investigation of stellar variability and rotation rates would also be useful for accurately measuring stellar ages with gyrochronology, and as a proxy for stellar activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, future work should include determining the depth of past searches for planets in these systems using archival photometry and public RV observations (e.g., Howard & Fulton 2016;Laliotis et al 2023). A follow-up investigation of stellar variability and rotation rates would also be useful for accurately measuring stellar ages with gyrochronology, and as a proxy for stellar activity.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the new generation of extreme-precision spectrographs, the RV measurement at sub-meter-per-second precision becomes feasible, including the Echelle SPectrograph for Rocky Exoplanets and Stable Spectroscopic Observations (ESPRESSO; Pepe et al 2010), the EXtreme PREcision Spectrograph (EXPRES; Jurgenson et al 2016), and NEID (Lin et al 2022). The previous investigations showed that the amplitude of RV variations resulting from stellar activity ranges in the order of a few meters per second (Hatzes 2002;Butler et al 2006Butler et al , 2017Lagrange et al 2010;Laliotis et al 2023). The dispersion in RV due to granulation is estimated to be larger than 0.3 m s −1 , significantly surpassing the signals emanating from terrestrial planets (approximately ∼0.09 m s −1 ).…”
Section: Introductionmentioning
confidence: 94%
“…Most recently, Laliotis et al (2023) returned to the target as part of a larger survey of Sun-like stars with host planets for potential direct imaging. They also argue that the signal is likely activity, as they find a significant Hα signal at a period of about 43.5 days, very close to the proposed Ma et al (2018) signal though not quite at the 42-day period, further placing the planet hypothesis into question.…”
Section: Previous Studiesmentioning
confidence: 99%